Answer:
5th term of sequence = -18
nth term of the sequence = -5n + 7
Explanation:
Difference between successive and previous term of the output,
= -3 - 2
= -5
Similarly,
![T_(3)-T_(2)=-8-(-3)](https://img.qammunity.org/2021/formulas/mathematics/high-school/evumru5lx2yqu6i020its72c92fq0wl175.png)
= -5
There is a common difference 'd' = (-5)
Therefore, the sequence formed will be an arithmetic sequence.
First term of the sequence 'a' = 2
Explicit formula of an arithmetic sequence,
= a + (n - 1)d [n = input value]
= 2 + (n - 1)(-5)
= 2 - 5n + 5
= -5n + 7
5th term of this sequence,
![T_(5)=2+(5-1)(-5)](https://img.qammunity.org/2021/formulas/mathematics/high-school/eslb9tc9tpt9yv6cir6050a58qr7fvdssj.png)
= 2 - 20
= -18
Therefore, 5th term of sequence = -18
nth term of the sequence = -5n + 7